Towards Greening Decisions on the University Campus: Initiatives, Importance and Barriers - Olaoluwa P. AASA; Olalekan Aquila JESULEYE; Modupe Olayinka AJAYI (International Journal of Engineering and Management Research, 2020)
Universities as ‘small worlds’ are veritable places for promoting environmental friendly activities; being breeding grounds for future decision makers. They are characterized by activities that negatively influence our environment which are in three areas which are: energy usage, waste generation and transportation. This study utilized both exploratory and survey designs to investigate the initiatives relating to training, research, campus operation and community service, their importance and barriers to effective implementation in The Federal University of Technology, Akure, Nigeria. The study found that implementing these initiatives has benefits associate with cost saving, employability, public image, quality assurance, and societal change. More than 70 percent of the respondents believed that implementing greening initiatives is very important. The study also revealed individual and institutional barriers in the achievement of this result. The most severe ones include: inadequate and sustainable awareness, ineffective policy, lack of knowledge and skills to handle relevant technology for greening. The study suggested that management should provide supports in the areas of policy-making and implementation, budgetary allocation and motivational structure to lead the way in the comity of universities.